1993
DOI: 10.1002/mc.2940080413
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of induction of osteocalcin gene expression on the presence of wild‐type p53 in a murine osteosarcoma cell line

Abstract: The p53 gene undergoes rearrangement in a high percentage of osteosarcomas, resulting in loss of its expression. A p53-null murine osteosarcoma cell line F6 was transfected with either a wild-type or a mutant p53 gene. Stably transfected cell lines were obtained, and their differentiation capabilities were compared in vitro with the parental cell line. Alkaline phosphatase and osteocalcin expression were measured as early and late differentiation markers, respectively. Induction of alkaline phosphatase express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 30 publications
(20 reference statements)
2
27
0
Order By: Relevance
“…In previous studies carried out with a murine osteosarcoma cell line showing characteristics of mature osteoblasts, we found that loss of p53 affects the ability of the cells to secrete osteocalcin, and that this property is regained after stable transfection of the cells with wild type p53 [7]. In other studies with osteoblast cell lines capable of displaying features of bone differentiation, we also observed p53 to have a distinct transcription-activating role, unrelated to growth arrest [33].…”
Section: Introductionsupporting
confidence: 56%
See 4 more Smart Citations
“…In previous studies carried out with a murine osteosarcoma cell line showing characteristics of mature osteoblasts, we found that loss of p53 affects the ability of the cells to secrete osteocalcin, and that this property is regained after stable transfection of the cells with wild type p53 [7]. In other studies with osteoblast cell lines capable of displaying features of bone differentiation, we also observed p53 to have a distinct transcription-activating role, unrelated to growth arrest [33].…”
Section: Introductionsupporting
confidence: 56%
“…the process of bone differentiation, osteoblasts proliferate, secrete matrix proteins and mineralize. We have found modulation of several bone specific genes to be related to the p53 status of the cell ( [7] and preliminary data).…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations